Study on gymnastics ring movements using force measuring system - Niu, J. Z.; Lu, X. M.; Xu, G.; Bin, L.; Li, L. (2021)
The purpose of this paper was to analyze five giant-swing phases performed on the rings using force-measuring system, which was synchronized with EMG and film. The results showed similar patterns in pulling force, shoulder angle, hip angle, hip velocity and ankle velocity when performing the movements of backward swing phase, dropped shoulder, giant-swing, and upward swing phase. The pulling-force changed from smaller than the body weight to greater than the body weight in the process of the backward swing. The first peak of pulling force occurred as shoulder drop phase ends. The second peak of pulling force occurred in the backward swing phase. The pulling force decreased gradually in the process of the upward swing. INTRODUCTION: Based on a paucity of research, it would appear that less attention has been placed on studying the movements performed on the rings in gymnastics. Reports on synchronized measurements on ring movements are lacking. The use of biomechanical analysis to determine the characteristics of this specialized routine will address the apparent deficiency. In this study, the force sensors, high speed cine-camera, and telemetry electromyography (EMG) were simultaneously operated by means of a synchronous signal generator in order to provide data on the specific series of movements performed on the rings. In this study, a different technique, namely internal synchronization was developed. This differed from the previous study where the external synchronization method was used. Therefor the purpose of this study was to explore the biomechanical characteristics of ring movements in order to provide additional knowledge of high performance gymnastics for both coaches and gymnasts. METHODS: Five male junior elite gymnasts at national level were selected as subjects to participate in this study. The age, body weight and body height of the subjects were 15.4 years, 43,9 kg and 154.8 cm respectively. A high-speed cine-camera (LBS-16A, China) operating at 100 Hz frequency was positioned at distance of 22.5m to the motion plane. A pulling force sensor (HLY-I/1000KG, China), was mounted between the strap of the rings and the steel rigging and was connected to the multi-function recorder through WHEATSTION- BRIDGE. This was used to record the force that the gymnasts exerted on the rings during movement. Telemetry surface EMG (Multi-Telemeter 551, Japan) was used to measure the EMG signals of muscles of gluteus maximus, biceps femoris and triceps during movements. The synchronization of filming, force measurement and EMG record was realized by triggering a synchronous signal generator. EMG and force signals were recorded by a microcomputer (Apple II) for further processing. The film materials were then analyzed on film motion analysis system (NAC MOVIES 100, Japan). Backward swing phase consisted of (1) Forward giant circle, (2) Backward swing to handstand, (3) Forward rotation of the shoulder, (4) Back up-rise, and (5) Backward swing in hang position. These movements were selected for analysis. This routine provides a basis for development of high degree of difficulty moves performed on the rings. RESULTS AND DISCUSSION: Some kinematics and kinetics measures associated with the phases in that the pulling forces were reduced to the minimum and are presented. The forward giant circle begins with handstand, thus the pulling force is the same as the body weight. As the forward swing phase begins, the center of gravity of the body moves away gradually from the point of support, the body swings forward to an angle of between ...